Plants and Humans in the Near East and the Caucasus: Ancient and Traditional Uses of Plants as Food and Medicine, a Diachronic Ethnobotanical Review - Miller, Naomi F. (Ethnobiology Letters, 2014)
Review of Plants and Humans in the Near East and the Caucasus: Ancient and Traditional Uses of Plants as Food and Medicine, a Diachronic Ethnobotanical Review (2 vols). Vol. 1: The Landscapes. The Plants: Ferns and Gymnosperms. Vol. 2: The Plants: Angiosperms. Diego Rivera Núñez, Gonzalo Matilla Séiquer, Concepción Obón, Francisco Alcaraz Ariza. 2011. Ediciones de la Unverisdad de Murcia. Pp. 1056. EUR 23.76 (paperback). ISBN 978-84-15463-07-08 (2 vols.), 978-84-15463-05-4 (vol. 1), 978-84-15463-06-1 (vol. 2).